Аssessment of the investment attractiveness of the oil and gas industry ("Journal "U". Economy. Management. Finance.", 2022)
The article presents of assessment of the investment attractiveness of several companies in the oil and gas industry of the Russian Federation by fundamental analysis. The fundamental undervaluation of shares of oil and gas companies creates a "value trap" for shareholders and does not increase the investment attractiveness of the industry.
Keywords: investment attractiveness; oil and gas companies; company shares; oil and gas industry; macroeconomic analysis; fundamental analysis; OPEC; sanctions